2021
DOI: 10.1186/s13756-021-00987-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of Staphylococcus aureus from the West African Dwarf (WAD) goat in Nigeria

Abstract: Background Staphylococcus aureus can colonize various host species, and human-animal interaction is a significant factor for cross-species transmission. However, data on S. aureus colonization in animals, particularly on ruminants in close contact with humans, is limited. The West African Dwarf (WAD) goat is among the earliest domesticated ruminant associated with rural dwellers and small-holder farmers in sub-Saharan Africa. This study aimed to investigate the population structure, antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 59 publications
5
10
1
Order By: Relevance
“…This observation supports the evidence of multiple introductions among MSSA isolates in sub-Saharan Africa as the basis for the evolution of this clone ( Baig et al, 2020 ). Recent studies have also reported CC152-MRSA from humans ( Egyir et al, 2020 , 2021 ) and animals ( Shittu et al, 2021 ), including fomites ( Shittu et al, 2020b ) in Africa. The emergence of PVL-positive CC152-MRSA is of public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…This observation supports the evidence of multiple introductions among MSSA isolates in sub-Saharan Africa as the basis for the evolution of this clone ( Baig et al, 2020 ). Recent studies have also reported CC152-MRSA from humans ( Egyir et al, 2020 , 2021 ) and animals ( Shittu et al, 2021 ), including fomites ( Shittu et al, 2020b ) in Africa. The emergence of PVL-positive CC152-MRSA is of public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…This rate is higher than those obtained previously (25%) by Guessennd [15]. In addition, similar studies carried out in 2012 in some African countries such as Morocco and Tunisia revealed 18.5% and 40.5% resistance to cefoxitin, respectively [16]. On the other hand, higher rates were observed in Senegal with 72% in 2012 [17].…”
Section: Discussionmentioning
confidence: 44%
“…Several studies identified t1236 in IMI cases in cattle [33][34][35][36][37]. The t1236 spa genotype is associated with CC97, frequently found in mastitis in cattle and harbors a high frequency of methicillin-resistant strains [38][39][40][41] In goat, sheep and deer, strains from CC97 have been isolated from the nares [30,[42][43][44][45][46].…”
Section: Resultsmentioning
confidence: 99%